Synthesis of large-area few layer graphene films by rapid heating and cooling in a modified apcvd furnace - David, Lamuel Abraham (Kansas State University, 2011)
Graphene because of its unique electrical (electron mobility = 2 x 10[superscript]5 cm[superscript]2 V[superscript]-1 s[superscript]-1), mechanical (E = 1 TPa), optical, thermal and chemical properties has generated a lot of interest among the research community in recent years. One of the most notable methods of synthesizing large area pristine graphene sheets, which are several 100 micrometers wide, is through thermal chemical vapor deposition (CVD). But very little has been known about the effects of heating and cooling rate of the substrate on the quality of graphene produced. Hence we varied various growth parameters to understand the process of graphene growth on Cu and Ni substrates when subjected to fast heating and quenching. This allowed optimization of the CVD process to achieve large-area graphene films consistently and repeatedly. This work provides new insights on synthesis of graphene at atmospheric pressures and the effect of (a) fast heating and fast cooling of substrates, (b) catalyst type and (c) gas flow rates on quality of the graphene produced. A carbon nanotube CVD furnace was restored and modified to accommodate graphene synthesis. We started with synthesis of graphene on Cu substrate following procedures already available in the literature (heating rate ~ 15 °C/min and cooling rate ~ 5 °C/min; total processing time 7 hours). This provided a good reference point for the particular furnace and the test setup. The best results were obtained for 15 minutes of growth at a CH4:H2 ratio of 1:30 at 950 °C. SEM images showed full coverage of the substrate by few layer graphene (FLG), which was indicated by the relatively high I[subscript]2D/I[subscript]G ratio of 0.44. The furnace was further modified to facilitate fast cooling (~4 °C/sec) of substrate while still being in inert atmosphere (Argon). The effect of growth time and concentration of CH[subscript]4 was studied for this modified procedure (at H[subscript]2 flow rate of 300 SCCM). SEM images showed full coverage for a CH[subscript]4 flow rate of 10 SCCM in as little as 6 minutes of growth time. This coupled with the fast cooling cycle effectively reduced the overall time of graphene synthesis by 7 times. The I[subscript]2D/I[subscript]G ratio in Raman spectrum was 0.4 indicating that the quality of graphene synthesized was similar to that obtained in conventional CVD. This modification also facilitated introduction of catalyst substrate after the furnace has reached growth temperature (fast heating ~8 °C/sec). Hence, the overall time required for graphene synthesis was reduced to ~6 % (30 minutes) when compared to the traditional procedure. SEM images showed formation of high concentration few layer graphene islands. This was attributed to the impurities on the catalyst surface, which in the traditional procedure would have been etched away during the long heating period. The optimum process parameters were 30 minutes of growth with 20 SCCM of CH[subscript]4 and 300 SCCM of H[subscript]2 at 950 °C. The Raman spectrum for this condition showed a relatively high I[subscript]2D/I[subscript]G ratio of 0.66. We also studied the effect of Ni as a catalyst. Similar to Cu, for Ni also, traditional procedure found in the literature was used to optimize the graphene growth for this particular furnace. Best results were obtained for 10 minutes of growth time with 120 SCCM of CH[subscript]4 in 300 SCCM of H[subscript]2 at 950 °C. SEM images showed large grain growth (~50 μm) with full coverage. The Raman spectrum showed formation of bi-layer graphene with a I[subscript]2D/I[subscript]G ratio of 1.03. Later the effect of growth time and concentration of the hydrocarbon precursor for Ni substrate subjected to fast heating (~ 8 °C/sec) was studied. It was found that because the process of graphene synthesis on Ni is by segregation, growth period or gas flow rate had little effect on the quality and size of the graphene sheets because of the presence of impurities on the substrate. This procedure yielded multilayer graphite instead of graphene under all conditions. Future work will involve study of changing several other parameters like type of hydrocarbon precursor and pressure in the chamber for graphene synthesis. Also various other substrates like Cu or Ni based alloys will be studied to identify the behavior of graphene growth using this novel procedure.
Keywords: Graphene synthesis; APCVD; Fast cooling; Fast heating; Copper; Nickel; Mechanical Engineering (0548); Nanoscience (0565); Nanotechnology (0652)